1996
DOI: 10.1164/ajrccm.154.2.8756834
|View full text |Cite
|
Sign up to set email alerts
|

Arm span-height relationships in patients referred for spirometry.

Abstract: Arm span has been proposed as a surrogate for standing height in the prediction of lung volumes in patients with thoracic deformities or who are unable to stand. The relationship between arm span and height has previously been reported as either a fixed ratio unaffected by age or as a regression equation in which the ratio varies as a function of age. We studied the relationship between standing height, arm span, race, sex, and age in 202 patients (ages 20 to 88 yrs) referred for screening spirometry. Multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
2
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 7 publications
6
53
2
2
Order By: Relevance
“…Most of the respondents classi®ed as undernourished (undernutrition de®ned as BMI1 8.5 kg/m 2 ) were actually mildly undernourished. Height not only declines with age (Dequeker et al, 1969;van Leer et al, 1992;de Groot et al, 1996;Parker et al, 1996), but is also dif®cult to measure accurately since many old people have problems standing upright and most walk with a slight bend at the hip and knees (Atchley, 1985). Thus ordinary BMI may underestimate the true prevalence of undernutrition in an elderly population.…”
Section: Anthropometric and Derived Measures By Agementioning
confidence: 99%
See 1 more Smart Citation
“…Most of the respondents classi®ed as undernourished (undernutrition de®ned as BMI1 8.5 kg/m 2 ) were actually mildly undernourished. Height not only declines with age (Dequeker et al, 1969;van Leer et al, 1992;de Groot et al, 1996;Parker et al, 1996), but is also dif®cult to measure accurately since many old people have problems standing upright and most walk with a slight bend at the hip and knees (Atchley, 1985). Thus ordinary BMI may underestimate the true prevalence of undernutrition in an elderly population.…”
Section: Anthropometric and Derived Measures By Agementioning
confidence: 99%
“…Individuals with a low BMI may encounter problems in responding to emergencies. Some studies have reported a decline in BMI with advancing age (Yassin & Terry, 1991;Parker et al, 1996;Strickland & Ulijaszek, 1993), while others have indicated otherwise (Carmelli et al, 1991). In this study, mean BMI was slightly lower in the oldest men and women.…”
Section: Nutritional Indicatorsmentioning
confidence: 99%
“…In males, arm span/1.03, and in women, arm span/1.01 was used for standing height in the regression equation. 17 …”
Section: What This Paper Contributes To Our Knowledgementioning
confidence: 99%
“…Arm span height (ASH; body height estimated from arm span) was calculated by algorithms from LINDERHOLM and LINDGREN [15] (ASHLinderholm) and PARKER et al [16] (ASHParker).…”
Section: Measurementsmentioning
confidence: 99%